Bioassay-guided fractionation and isolation of Arctigenin from Saussurea heteromalla for in vitro and in silico cytotoxic activity against HeLa cells. (January 2022) - Batool, Azra; Miana, Ghulam Abbas; Alam, Mahboob; Khan, Muhammad Tariq; Muddassir, Muhammad; Zaman, Wajid; Saifullah Khan,; Aman, Akhtar; Khusro, Ameer; Arasu, Mariadhas Valan; Al-Dhabi, Naif Abdullah; Choi, Ki Choon; et al.
Abstract: Ethnopharmacological relevance of Saussurea species to anticancer compounds instigated the present research. Therefore to search the bioactive anticancer lead compound (s) scientifically bioactivity guided fractionation of Saussurea heteromalla (Compositae) was carried out that resulted in the isolation and characterization of three butyrolactone (lignan) secondary metabolites i.e. arctigenin (1), arctiin (2) and matairesinol (3). Compounds (1) and (2) were already reported in S. heteromalla, whereas compound (3) is isolated for the first time in present study. Moreover in vitro antiproliferative activity of arctigenin against HeLa cells (IC50: 11.04 μg/ml) along with its docking against two HeLa proteins cellular tumor antigen p53 " − 7.31 kcal/mol" and NF-κB " − 6.31 kcal/mol" are reported here for the first time. These docking results support the cytotoxic potential of arctigenin and authenticate it as valuable drug for cervical cancer. Based on cytotoxic activity and docking results compound (1) is striking substrate for further research to explore its mechanism of action in vivo . The structure of three compounds was elucidated by the interpretation of their ESI-MS, 1 H and 13 C NMR, FT-IR and UV results and by comparison to the already published data. Graphical abstract: Image 1 Highlights: Bio guided fractionation of Saussurea heteromalla resulted in three butyrolactones—arctigenin, arctiin and matairesinol. Arctigenin was identified as cytotoxic bioactive lead molecule. Docking studies of arctigenin against p53 and NF-κB authenticated its potential against cervical cancer.